Fifty-four things wrong with Gwendolyn Rogers - Carter, Caela (Quill Tree Books, an imprint of HarperCollinsPublishers, 2021)
"A chronically frustrated eleven-year-old girl named Gwendolyn Rogers comes to realize she has an undiagnosed mental health issue and tries every way possible to get control of her emotions"--